2020
DOI: 10.1016/j.nuclphysa.2020.121692
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Coulomb interaction on parameters of resonance states in mirror three-cluster nuclei

Abstract: We investigate how the Coulomb interaction affects the energy E and width Γ of resonance states in mirror nuclei. We employ a three-cluster microscopic model to determine position of resonance states in two-and three-body continua. Two parameters are introduced to quantify effects of the Coulomb interactions. As the energy and width of the corresponding resonance states of mirror nuclei are displayed on an E-Γ plane, these parameters determine a rotation and a dilatation. With the help of these parameters we f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The energy E of the resonance states are measured from the α + d threshold. Results of our calculation with the MP and the MHNP are compared with the experimental data [12][13][14]. There is a fairly good agreement between the theoretical and experimental data.…”
Section: The Capture Reaction α + D =mentioning
confidence: 69%
“…The energy E of the resonance states are measured from the α + d threshold. Results of our calculation with the MP and the MHNP are compared with the experimental data [12][13][14]. There is a fairly good agreement between the theoretical and experimental data.…”
Section: The Capture Reaction α + D =mentioning
confidence: 69%
“…It was shown that the relation between wave function and expansion coefficients ( 20) is valid even for small values of n (n ≥ 5). In present calculations we use similar relations for the expansion coefficients of the asymptotic wave functions (12) for charged clusters.…”
Section: Methodsmentioning
confidence: 99%